Science centre engagement on visitor personal connection - Baniyamin, Nurhaya; Abdul Rahim, Zaiton (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Museum exhibition environment provides experiential learning through its messages to influence knowledge, attitudes and learning behaviours of visitors. Connections in visitors' cognitive, affective, emotional and physiological responses play a beneficial role in museum visits. The research focuses on how science centre as part of a museum discusses various practical methods to inspire visitor into having a response. The review features multiple theories of learning advocating how visitors learn and how these theories influence a museum’s exhibition design endeavors. Using the experience of selected Science Centres as primary case-studies, this article analyses various perspectives and organizational approaches. Cultivating visitor interest through visitor personal connection represents an important echoing concept which reaches at the essence of the exhibition design practice. Visitors act as celebrants of science information in an edutainment context, motivated by a quest for social and enlightening experiences. How does science centre engage in visitor personal connection? How do they sustain quality visitor experience and informal learning objectives? Responses to these queries are the core of this article.